PUSAT PEMANFAATAN DAN KONSERVASI TAILING KUTO PANJI - Steffi Setiawan; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2021)
The tin mining in Bangka Belitung Province has been exploited for the past three centuries, this exploitation activity disrupts the landscape and causes environmental impacts. The resulting environmental impact is an increase in temperature and humidity. The landscape in the ex-tin mining area shows two surface forms, namely: tailings and underneath. Tailings are the residue left over from leaching of tin minerals, and underneath are shaped like ponds or small lakes. The structure of the soil layer in the former tin mining area is not like the soil structure in general, the topsoil in the former tin mining area has generally been lost, and the soil fertility is low with high levels of the sand fraction.Areas that have been exploited must be reclaimed and revegetated, so that it is safe to visit. One of the wastes from tin mining activities, namely tailings, has made Bangka Belitung Province a producer of tailings, the tailings can be reused as material for brick making, but before processed into brick material, it is necessary to separate the tailings from hazardous materials using a magnetic separator so that it is safe to become one of the brick-making materials. For further research on other uses of the ex-tin mining area, a conservation area is needed. Other than that, it is a place of recreation and education, in the form of elevated trails that surround the tin mine reclamation area with surrounding areas of former tin mines, shrimp pond that was previously a former tin mining area, and tropical rainforest.The design approach used in this planning is to make the traditional house of the Lom Tribe as a reference for the application of tropical architecture. Through this approach, it produces natural ventilation of the new composition. In addition, this design concept also adds sun shading and courtyard as part of tropical architecture. Keywords: ex-mining site; conservation; revegetation; reclamation; the traditional house of Lom TribeAbstrakTambang timah di Provinsi Bangka Belitung sudah sejak tiga abad lalu di eksploitasi, kegiatan eksploitasi ini mengakibatkan terganggunya lanskap dan menimbulkan dampak lingkungan. Dampak lingkungan yang ditimbulkan adalah peningkatan suhu, dan kelembaban. Lanskap pada area bekas tambang timah memperlihatkan dua bentuk permukaan, yaitu: tailing dan kolong. Tailing merupakan sisa dari pencucian mineral timah dan kolong berbentuk seperti kolam atau danau kecil. Struktur lapisan tanah pada area bekas tambang timah tidak seperti struktur tanah pada umumnya, lapisan tanah bagian atas atau top soil pada area bekas tambang timah umumnya sudah hilang, dan kesuburan tanah menjadi rendah dengan tingginya kadar fraksi pasir.Area yang sudah di eksploitasi harus direklamasi dan direvegetasi agar aman untuk dikunjungi. Salah satu limbah dari kegiatan tambang timah yaitu tailing, maka menjadikan Provinsi Bangka Belitung sebagai produsen hamparan tailing, tailing tersebut dapat dimanfaatkan kembali menjadi bahan pembuatan batako, namun sebelum diolah menjadi bahan batako, perlu dilakukan pemisahan tailing dengan bahan yang berbahaya menggunakan magnetic separator sehingga aman untuk menjadi salah satu bahan pembuatan batako. Untuk penelitian lebih lanjut pemanfaatan lain dari area bekas tambang timah, maka diperlukannya tempat konservasi. Selain itu, menjadi tempat rekreasi dan edukasi berupa elevated trails yang mengitari area reklamasi tambang timah dengan sekelilingnya terdapat area bekas tambang timah, tambak udang yang sebelumnya adalah area bekas tambang timah, dan tropical rainforest.Pendekatan desain dalam perencanaan ini adalah dengan menjadikan rumah adat Suku Lom sebagai acuan dari penerapan arsitektur tropis. Melalui pendekatan tersebut menghasilkan pengudaraan alami dari bentuk gubahan baru. Selain itu konsep perancangan ini juga menambahkan sun shading dan courtyard sebagai bagian dari arsitektur tropis.